Memperkuat Ketahanan Ekonomi Kabupaten Pesisir Selatan Melalui Posisi Tawar Pelaku Usaha Pertanian dan Perikanan - Sovia Dewi (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
This study examines the structural vulnerability of regional economic resilience in Kabupaten Pesisir Selatan, Indonesia, focusing on the weak bargaining position of small-scale food crop farmers and fishers within market structures. It analyzes how the predominance of producers as price takers contributes to unstable household income and regional economic fragility, and formulates policy directions to strengthen their market position. The research employs a qualitative policy analysis using a desk study approach. Data were collected from official statistics, government planning documents, regulatory frameworks, and relevant academic literature. The main issue was identified through the Urgency, Seriousness, and Growth (USG) method, while alternative policies were evaluated using Dunn’s criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and feasibility. The findings indicate that economic vulnerability is driven more by structural market constraints than by low production levels. Limited market access, weak economic institutions, dependence on intermediaries, and minimal value addition reinforce producers’ position as price takers. Among the evaluated alternatives, strengthening collective marketing through producer economic institutions such as farmer groups and cooperatives emerges as the most feasible and effective strategy. The study concludes that institutional strengthening and market structure reform are more relevant than production-oriented interventions alone in enhancing regional economic resilience. However, further empirical research is needed to assess implementation dynamics at the local level.